Psychosocial Foundations for Pedagogical Skills Formation of Future Specialists in the Special Educational Environment - Sydykova, Roza Sh.; Yussupova, Adalyat A.; Berekeshev, Galimzhan K.; Smailova, Torgyn A.; Kuldanov, Nauryz T. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The main goal of the work is to analyse future music teachers’ pedagogical process and its impact on the creative potential of the individual. Background: Pedagogical work has always been creative since its main purpose is to build, create a personality, develop, affirm the spiritual principle in a person. In addition, the activities of a teacher are carried out in constantly changing situations, requires consideration of all conditions. Therefore, the main task of a teacher is to transfer his creative potential with special educational needs. Method: theoretical methods were used for research, which allowed us to determine the role of music in students’ development. Results: It was established that the formation of artistry in the process of teaching vocals is understood as a complex motivational-semantic education. It has been determined that the strength of the students’ spiritual attraction to their mentor largely depends on the presence in his individual appearance of such a purely personal quality as an attraction, introduced by psychologists in scientific use for more in-depth ideas about the artistic and communicative possibilities of a person. Conclusion: The results of the study made it possible to determine that an integrated approach to musical and pedagogical activity helps to solve pedagogical problems using musical art tools that combine a complex of special, psychological and pedagogical, general scientific, methodological knowledge, skills with the leading role of general pedagogical abilities.